What could go wrong? Conceptual understanding and exploration of maladaptation in Swedish municipalities - Rublovska,Agate; Bergh,Rebecka (2025)
Adaptation strategies can backfire and cause maladaptive outcomes, yet this is an understudied area in Swedish adaptation work, and a conceptually challenging theme with potential justice implications. The study explored the potential existence of maladaptation in Swedish municipalities in the Motala ström catchment area in collaboration with the FairWater research project, through conducting 18 qualitative interviews with officials from municipalities and county administrative boards. While almost half of the respondents did not consider negative consequences from adaptation work, cost and spatial trade-offs were the most commonly cited. More traditional maladaptation aspects, such as rebounding vulnerability, shifting vulnerability, increasing emissions, and path dependency were often not equated with ‘negative consequences’ but rather mentioned spontaneously at other points in the interviews. Few overlaps were seen in the respondents’ associations of unsuccessful and unfair adaptation, highlighting a lack of justice considerations in municipal CCA. A wide array of adaptation constraints was highlighted by the participants including governance; budgetary constraints; political will; trade-offs; legal framework; monitoring, evaluating and learning; and complexity. While not all constraints were said to directly lead to maladaptation, they have the potential to do so. With few studies of maladaptation done previously in Sweden, the maladaptation indicators mapped in this study potentially suggest a large hidden number of maladaptation risks. Based on the study’s results, future research could benefit from testing monitoring, evaluation and learning frameworks to avoid maladaptation in a Swedish municipal context and assess if using such frameworks aids decision-making.
Keywords: Climate change; climate change adaptation; maladaptation; Sweden; municipalities